Placebo effects of caffeine on cycling performance - Beedie, C. J.; Stuart, E. M.; Coleman, D. A.; Foad, A. J. (Medicine & Science in Sports & Exercise, 2006)
Purpose: The placebo effect-a change attributable only to an individual's belief in the efficacy of a treatment-might provide a worthwhile improvement in physical performance. Although sports scientists account for placebo effects by blinding subjects to treatments, little research has sought to quantify and explain the effect itself. The present study explored the placebo effect in laboratory cycling performance using quantitative and qualitative methods.